Microstructural Evolution and ORR Activity of Nanocolumnar Platinum Thin Films with Different Mass Loadings Grown by High Pressure Sputtering. Issue 13 (5th October 2020) - Ergul-Yilmaz, Busra; Yang, Zhiwei; Perry, Mike L.; More, Karren L.; Macauley, Natalia; Borup, Rod L.; Karabacak, Tansel
Abstract : Nanocolumnar platinum thin films (Pt-TFs) with different Pt mass loadings were grown by high pressure sputtering (HIPS) and investigated as oxygen reduction reaction (ORR) electrocatalysts for polymer electrolyte membrane fuel cell applications. Mass loading was controlled by changing the sputter deposition time. A cauliflower-like columnar microstructure was achieved by depositing the Pt-TFs onto a microporous layer (MPL)-like surface composed of carbon particles in order to mimic catalyst-coated gas diffusion electrodes. Microstructural evolution of HIPS Pt-TFs and their ORR activity were investigated. Electrochemical characterization of the nanocolumnar Pt-TFs was performed by cyclic voltammetry and rotating disk electrode measurements on Pt-TF/MPL-like-layer/glassy-carbon samples in an aqueous perchloric acid electrolyte. The electrochemically active surface area increased from 18 to 39 m 2 g −1 as the Pt mass loading was decreased. Specific activity of the films was similar (∼600 μ A cm −2 ) for all Pt mass loadings, due to the similar nanoparticle sizes of ∼5 nm as observed by transmission electron microscopy and X-ray diffraction. Mass activity of the films increased from 0.11 to 0.26 A mg −1 as the Pt mass loading was decreased, which is an indication of the effective Pt utilization and better access through the catalyst layer at lower Pt mass loadings.